INVESTIGATING OF KINEMATIC AND DYNAMIC PARAMETERS OF VIBROSIEVES - Бережницький, Богдан Степанович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Calculating model and method of investigating kinematic and dynamic parameters of vibrosieves have been worked out. Mathematical dependence of constructive and operative vibrosieves working parameters on their characteristics has been received. Comparing calculated trajectory of moving points (Lissazh curves) with experimental ones confirm the correspondence of suggested model to real one. Changing of their forms is a signal of breaking project operating work of the sieve under the influence of vibroframe disbalance, changing rigility of based springs and rate of vibroshaft rolating. The suggested methods and results can be applied for projecting new examples of vibrosieves. They also allow to conduct reliable control of their operating work.